THE IMPACT OF JOB SATISFACTION, COMMUNICATION AND COMPENSATION TOWARDS EMPLOYEE PERFORMANCE AT PT. PEGADAIAN (PERSERO) IN TANGERANG AREA - Febrinol, Febrinol; Herminingsih, Anik (Dinasti International Journal of Digital Business Management, 2021)
The research purpose was to revealed and described those impact which is from job satisfaction, communication and compensation towards employee performance at PT. Pegadaian (Persero) in Tangerang Area. The method that used on this research was an explanatory survey to explain and described the phenomena which occured through examining the impact which occured between variables, the research population was 150 people with sample of 109 employees at PT Pegadaian (Persero) in Tangerang Area which consisting of collateral appraisers, cashiers and from micro credit department. Data collection techniques by the surveys through questionnaires, interviews and observations. The analysis method that used was descriptive statistical analysis, validity and reliability test, classic assumption test, which includes normality test, heteroscedasticity test, multicolonierity test and hypothesis test through multiple linear regression analysis techniques which processed by the SPSS 25 program. The results from this research was illustrated that both partially and simultaneously the job satisfaction, communication and compensation have an impact towards employee performance at PT. Pegadaian (Persero) in Tangerang Area.